An Overview of Home Stay at Antu Tourism Area of Ilam District - Bhattarai, Rabi Kumar; Adhikari, Binay (Journal of Business and Social Sciences, 2021)
The tourism of Nepal is based on three main aspects (service, facility and attraction). Home stay tourism is an emerging tourism concept evolved lately in the tourism industry. ’Guest is god’ is the belief of typical Nepalese society which has been carrying out the concept of homestay tourism in Nepal.For its multifaceted potentiality, Nepal can become a model homestay. Homestay activities provide clients with a wealth of natural resources, man-made heritages, ethno-cultural wealth, innocent environments, and pleasant hospitality, among many other unexplored resources.Based on the primary and secondary sources of data, the article is assessing the home stay tourism in Antu area. The objective of this article is to find out the major motivational factors, available accommodation services and challenges of homestay activities. The article is used for exploratory and descriptive research designs on the basis of its objectives. The study attempts to explore the assessment of home stay tourism in Antu area and it concludes that income and employment is a main motivating factor for operation of home stay service. The accommodation services are different in nature and capacity, and the study also identifies the major challenging factors for home stay in the Antu area.